Electrochemical Behavior of CsI in LiCl Molten Salt - Sung-Wook Kim; Sang-Kwon Lee; Min Ku Jeon; Eun-Young Choi (Science and Technology of Nuclear Installations)
The electrochemical behavior of CsI in LiCl molten salt was investigated to identify its impact on the electrolytic oxide reduction of oxide-phase spent nuclear fuels by combined electrolysis and cyclic voltammetry experiments of LiCl-CsI in comparison with LiCl, LiCl-CsCl, and LiCl-LiI. It was found that Cs+ ions were hardly involved in the cathode reaction, and reduction of Li+ ions occurred dominantly in the cathode. In contrast, incorporation of I− ions induced low-potential anode reaction compared with the I− ion-free cases. Such additional electrochemical reaction resulted in the generation of I2 and/or ICl gases, which would increase a process burden for treating 129I with exceptionally long lifetime. In this respect, separating CsI from spent nuclear fuel before the electrolytic oxide reduction is recommended for the purpose of efficient waste management.